1978
DOI: 10.1042/bj1750289
|View full text |Cite
|
Sign up to set email alerts
|

Effects of zinc ion on the conformation of antigenic determinants on insulin

Abstract: Comparison of c.d. spectra of Zn-insulin with Zn2+-free insulin demonstrated significant differences. It has been proposed that these differences are due to either changes in the structure of insulin monomers within aggregated insulins or the results of insulin aggregation. The effect of Zn2+ on the immunological activity of insulin indicated that the antigenic determinants of insulin were also altered. The apparent loss of immunological activity of monoiodotyrosylinsulin was demonstrated to be due to the loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
3

Year Published

1981
1981
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 25 publications
0
12
0
3
Order By: Relevance
“…Furthermore, kinetics and ion concentration required for mitogenic responses to free zinc are different than the response to insulin (30 and unpublished observations). Antibody studies also support the concept that immunoreactive determinants on the molecules are present in zinc-dependent conformations (31,32). In studies with insulin antisera not only was zinc-free insulin shown to have marked decreased immunologic activity at concentrations where insulin was thought to be monomeric (31), but it was also shown that addition of zinc restored immunologic activity (32).…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Furthermore, kinetics and ion concentration required for mitogenic responses to free zinc are different than the response to insulin (30 and unpublished observations). Antibody studies also support the concept that immunoreactive determinants on the molecules are present in zinc-dependent conformations (31,32). In studies with insulin antisera not only was zinc-free insulin shown to have marked decreased immunologic activity at concentrations where insulin was thought to be monomeric (31), but it was also shown that addition of zinc restored immunologic activity (32).…”
Section: Resultsmentioning
confidence: 67%
“…Antibody studies also support the concept that immunoreactive determinants on the molecules are present in zinc-dependent conformations (31,32). In studies with insulin antisera not only was zinc-free insulin shown to have marked decreased immunologic activity at concentrations where insulin was thought to be monomeric (31), but it was also shown that addition of zinc restored immunologic activity (32). Recognition of similar zinc-dependent immunogenic determinants by human lymphocytes is one potential explanation for the extensive cross-reactivity between human and animal insulins.…”
Section: Resultsmentioning
confidence: 67%
“…Structurally, the addition of zinc to insulin results in conformational changes, which have been detected by ultraviolet circular dichoric spectroscopy [38]. It has been reported that the removal of zinc alters the ternary structure of insulin and can reduce the immunological insulin activity due to the changes in antigenic determinations of insulin [39,40]. The zinc contents of diabetic pancreases have been reported to be depressed when compared to normal ones [41], and diabetic children have been shown to have low hair zinc levels, which return to normal after insulin administration [42].…”
mentioning
confidence: 99%
“…Other antibodies, such as the MA-FTS monoclonal antibody or some of the antibodies contained in the rabbit polyclonal antithymulin antiserum, produced against synthetic thymulin and screened by ELISA or RIA, recognize the peptide independently of the presence of zinc. Interestingly, the existence of zinc-dependent antigenic determinants has also been suggested for insulin (16). A metal-dependent epitope has also been reported for the prothrombin molecule (17).…”
Section: Discussionmentioning
confidence: 93%